Revitalise* a moment in time : celebrating international women's day 2007 - Chen, Serene Meihua (2008)
This report presents the team’s collaboration with Singapore Council of Women’s Organisations (SCWO) in a practical application of an Integrated Marketing Communications strategy to the celebrations of International Women’s Day 2007 (IWD 2007). The Revitalise* A Moment in Time campaign was conceptualised and executed to engage targeted publics under the theme of Traditions. The team’s efforts in public relations yielded a total Advertising Equivalent Value (AEV) of $231,773.71. This report includes an effort in formative research that directed the communications plans, strategies and execution, and concludes with an evaluation of the campaign’s effectiveness.